Acquired Vitamin K Deficiency as Unusual Cause of Bleeding Tendency in Adults: A Case Report of a Nonhospitalized Student Presenting with Severe Menorrhagia - Omid Reza Zekavat; Gholamreza Fathpour; Sezaneh Haghpanah; Seyed Javad Dehghani; Maryam Zekavat; Nader Shakibazad (Case Reports in Obstetrics and Gynecology)
We report a rare case of acquired vitamin K deficiency presenting with severe menorrhagia and without any gynecological problem. Partial thromboplastin time (59.2 seconds) and prothrombin time (33.1 seconds, INR: 5.97) were considerably prolonged in laboratory evaluations. A complete coagulation factor assay test was performed for the patient: factor IX, 24%; factor II, 41%; factor VII, 3%; and factor X, 52%. She had been taking many high-energy drinks and she had inadequate dietary intake for the past 6 months. Given that she had vitamin K deficiency (VKD), a course of vitamin K therapy was started for her in the hospital. This case showed the potential for menorrhagia due to VKD with use of high-energy drinks and the value of a complete and detailed history in early diagnosis.